Subcutaneous Adipose Tissue Accumulation Is an Independent Risk Factor of Urinary Stone in Young People - Ye, Zixing; Xiao, He; Liu, Guanghua; Qiao, Yi; Zhao, Yi; Ji, Zhigang; Fan, Xiaohong; Li, Rongrong; Wang, Ou (Frontiers in Endocrinology, 2022)
Background: Urinary stones usually start at a young age and tend to recur. Therefore, preventing stone occurrence and recurrence in young people is crucial. We aimed to investigate the association between subcutaneous adipose tissue, visceral adipose tissue, and stone episodes in young people. Methods: We retrospectively studied patients aged below 40 years with kidney or ureteral stones. Data on demographic and metabolic characteristics, urolithiasis history, subcutaneous fat area (SFA), and visceral fat area (VFA) were collected. We evaluated the association between SFA or VFA and the occurrence or recurrence of stone episodes using binary logistic regression and Poisson regression analyses. Results: In total, 120 patients were included. Abdominal obesity, overweight or obesity, dyslipidemia, metabolic syndrome, SFA, and VFA increased with the number of stone episodes (all p 0.05). The increase in SFA was independently associated with episode occurrence (p = 0.015). Patients with an SFA 97 cm2 had a higher risk of episode occurrence. SFA and VFA accumulation were independently associated with episode recurrence (all p 0.05), and SFA had a stronger association than VFA did. Conclusions: In young people, SFA accumulation is an independent and early risk factor for the occurrence and recurrence of stone episodes. Subcutaneous fat could be a convenient and effective indicator to assess the risk of stone episodes before the development of metabolic disorders.